Exploring the Effects of Game-based Learning - Mondal, Anowar Hussain; Maity, Ranjan (Journal of Engineering Education Transformations, 2025)
Advancements in technologies are helping the education system to improve and explore a new dimension of learning. Learning beyond class hours is an important issue. Traditional textbooks and learning materials (online as well as offline) may help to overcome this challenge for theory-based papers. On contrary, experimenting in a lab beyond the class hour is challenging, more specifically in schools. The effect of the COVID pandemic also forced the researchers to explore new ways of learning, particularly in lab work. In this work, an interactive virtual Lab was developed for school students. They can virtually perform Ohm’s Law experiments using a mobile phone or computer. The proposed lab was designed using Unity Engine with C#. In order to check the acceptance of the proposed applications, we conducted a usability evaluation. It was observed that students learned more effectively using our proposed application.